PARTISIPASI ORANG TUA DALAM MENINGKATKAN MOTIVASI ANAK MENGIKUTI PELAJARAN AGAMA KATOLIK DI SDN 1 LEBO - Eriana Anugrahni; Timotius Tote Jelahu; Fransiskus Janu Hamu (Sepakat : Jurnal Pastoral Kateketik, 2019)
This study aims to determine the participation of parents in increasing children's motivation to attend Catholicism at SDN 1 Lebo, knowing parents' understanding of participation, forms of parental participation, and inhibiting and supporting factors of parental participation. Through this scientific work, parents are expected to be more able to participate in motivating children, determine the efforts that will be made and find out implications or benefits from parental participation in increasing children's motivation to attend Catholic religion in SDN 1 Lebo. This study uses qualitative research. The data obtained through interviews with informants and documentation. The research location is at SDN 1Lebo, the parish of St Petrus and PaulusAmpah.As for the research steps include determining the theme, guide the interview with the informants, reflection, implications and synthesis.